X+(x-5)+(2x)=59

Simple and best practice solution for X+(x-5)+(2x)=59 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+(x-5)+(2x)=59 equation:


Simplifying
X + (x + -5) + (2x) = 59

Reorder the terms:
X + (-5 + x) + (2x) = 59

Remove parenthesis around (-5 + x)
X + -5 + x + (2x) = 59

Reorder the terms:
-5 + X + x + (2x) = 59

Combine like terms: x + (2x) = 3x
-5 + X + 3x = 59

Solving
-5 + X + 3x = 59

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + X + 5 + 3x = 59 + 5

Reorder the terms:
-5 + 5 + X + 3x = 59 + 5

Combine like terms: -5 + 5 = 0
0 + X + 3x = 59 + 5
X + 3x = 59 + 5

Combine like terms: 59 + 5 = 64
X + 3x = 64

Add '-3x' to each side of the equation.
X + 3x + -3x = 64 + -3x

Combine like terms: 3x + -3x = 0
X + 0 = 64 + -3x
X = 64 + -3x

Simplifying
X = 64 + -3x

See similar equations:

| 3-7+12w=10w+30+2 | | x(4x+10)=0 | | 3-7+5+13-2= | | 3a+4b-5c= | | 5y-3=12y+60 | | 14x+16=3(x-1) | | 72c-108=7c-3 | | 6x=24x+36 | | 6x-3=1.222 | | -2,992+272m=0 | | 20+2x=2.50x | | f=5+0.20d | | .778(6x-3)=2 | | 2726=29(p+35) | | 3ot-20=70 | | 16-7t=6-5t | | 3x+4-6x+2= | | -3(x-6)=-3 | | -2x^2-6x+3=0 | | 4x-3*-17=26 | | -8(2t+7)=-136 | | 25=x+x(.323) | | (4x-7)=2 | | 2(f-5)=-16 | | 52=2v+16 | | 180x+75y=165 | | -2(x^2+3x+9)+3-9=0 | | -4q-17=-6q+43 | | 10d+d-9d-d=17 | | 3x+23=-2x-7 | | 3(4x+2)=10x-2 | | 14x-5=6x+1 |

Equations solver categories